2009
DOI: 10.1029/2008ja013556
|View full text |Cite
|
Sign up to set email alerts
|

Computing magnetospheric equilibria with anisotropic pressures

Abstract: [1] We present initial results from an equilibrium code that has been modified to include the effect of anisotropic pressures. This equilibrium code uses a frictional technique to iterate a set of modified MHD equations to equilibrium. We describe the modifications made to the original isotropic equilibrium code, including changes to the initial conditions that include a procedure to enforce the specified anisotropy with the restriction that the total energy on a flux tube be conserved. This allows ready compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Zaharia et al [] fed their 3‐D equilibrium code with anisotropic pressure in the equatorial plane from the UNH‐RAM ring current model [ Jordanova et al , ] and analyzed the computed magnetic fields and electric fields during a geomagnetic storm. Wu et al [] extended another equilibrium code RCM‐E, which has already coupled with the RCM, to include anisotropic pressure. They also proposed the possibility of coupling the equilibrium code with the CRCM.…”
Section: Introductionmentioning
confidence: 99%
“…Zaharia et al [] fed their 3‐D equilibrium code with anisotropic pressure in the equatorial plane from the UNH‐RAM ring current model [ Jordanova et al , ] and analyzed the computed magnetic fields and electric fields during a geomagnetic storm. Wu et al [] extended another equilibrium code RCM‐E, which has already coupled with the RCM, to include anisotropic pressure. They also proposed the possibility of coupling the equilibrium code with the CRCM.…”
Section: Introductionmentioning
confidence: 99%
“…Zaharia et al [2004] computed 3-D force-balanced magnetospheric configurations with their 3-D equilibrium code and applied to magnetic storm simulations. Wu et al [2009] extended a friction code equilibrium solver to include pressure anisotropy. These studies provide very interesting insight of how anisotropic pressures modify the magnetic field and current configuration in the inner magnetosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The coupled MHD‐RCM code showed significantly higher inner magnetospheric particle pressures and strong region 2 Birkeland currents, as well as partial shielding of the inner magnetosphere from the main force of the convection electric field [ De Zeeuw et al , 2004]. Preliminary results from RCM‐E that was modified to include the effect of anisotropic pressures were presented by Wu et al [2009]. Using one‐dimensional empirical fits to observed plasma pressure anisotropies [ Lui et al , 1994], it was found that the magnetic field may increase in the anisotropic case as much as 30% near the equatorial plane in the transition region between the inner magnetosphere and the magnetotail.…”
Section: Introductionmentioning
confidence: 99%